Anticoagulant effects of phytotherapeutic drugs and their importance in surgical dental procedures - Machado, Ricardo; Silva, Leopoldo Cosme; Cuba, Leticia De Freitas; Oliveira, Jonatas Rafael De; Martinho, Frederico Canato; Ferrari, Carlos Henrique (Faculdade São Leopoldo Mandic, 2017)
ABSTRACT Phytotherapeutic drugs are plant-derived products with medicinal properties. They are used for treating or preventing several diseases. However, patients who use these substances and even health professionals are unaware of their negative effects. One of the most common negative effects of phytotherapeutic drugs reported in the literature is the inhibition of natural coagulation factors in the human body. Therefore, the aim of this study was to perform a brief review of the literature concerning the anticoagulant effects of phytotherapeutic drugs and their importance in surgical dental procedures. Preventive measures, clarification and monitoring of patients taking phytotherapeutic drugs are recommended before performing surgical dental procedures, in order to prevent against complications such as hemorrhage.

RESUMO Fitoterápicos são produtos derivados de plantas com propriedades medicinais. Eles são utilizados para o tratamento ou a prevenção de diversas doenças. No entanto, os pacientes que fazem uso destas substâncias, na sua grande maioria, desconhecem seus efeitos negativos. Portanto, o objetivo deste estudo foi realizar uma breve revisão de literatura sobre os efeitos anticoagulantes de fitoterápicos e sua importância diante da realização de procedimentos odontológicos cirúrgicos. Medidas de prevenção, esclarecimento e acompanhamento de pacientes que se utilizam destes medicamentos são recomendados antes da realização destes procedimentos a fim de prevenir complicações como processos hemorrágicos.
Efeitos anticoagulantes de drogas fitoterapicas e sua importância em procedimentos odontológicos cirúrgicos
Keywords: Blood coagulation factors; Phytotherapeutic drugs; Surgical dental procedures; Fatores de coagulação sanguínea; Fitoterápicos; Procedimentos odontológicos cirúrgicos.